Household preferences and willingness to pay for health insurance in Kampala City: a discrete choice experiment - Edward Kalyango; Rornald Muhumuza Kananura; Elizabeth Ekirapa Kiracho (Cost Effectiveness and Resource Allocation, 2021)
Abstract Introduction Uganda is in discussions to introduce a national health insurance scheme. However, there is a paucity of information on household preferences and willingness to pay for health insurance attributes that may guide the design of an acceptable health insurance scheme. Our study sought to assess household preferences and willingness to pay for health insurance in Kampala city using a discrete choice experiment. Methods This study was conducted from 16th February 2020 to 10th April 2020 on 240 households in the Kawempe division of Kampala city stratified into slum and non-slum communities in order to get a representative sample of the area. We purposively selected the communities that represented slum and non-slum communities and thereafter applied systematic sampling in the selection of the households that participated in the study from each of the communities. Four household and policy-relevant attributes were used in the experimental design of the study. Each respondent attended to 9 binary choice sets of health insurance plans that included one fixed choice set. Data were analyzed using mixed logit models. Results Households in both the non-slum and slum communities had a high preference for health insurance plans that included both private and public health care providers as compared to plans that included public health care providers only (non-slum coefficient β = 0.81, P < 0.05; slum β = 0.87, p < 0.05) and; health insurance plans that covered extended family members as compared to plans that had limitations on the number of family members allowed (non-slum β = 0.44, P < 0.05; slum β = 0.36, p < 0.05). Households in non-slum communities, in particular, had a high preference for health insurance plans that covered chronic illnesses and major surgeries to other plans (0.97 β, P < 0.05). Our findings suggest that location of the household influences willingness to pay with households from non-slum communities willing to pay more for the preferred attributes. Conclusion Potential health insurance schemes should consider including both private and public health care providers and allow more household members to be enrolled in both slum and non-slum communities. However, the inclusion of more HH members should be weighed against the possible depletion of resources and other attributes. Potential health insurance schemes should also prioritize coverage for chronic illnesses and major surgeries in non-slum communities, in particular, to make the scheme attractive and acceptable for these communities.